Pedicularis munzurdaghensis (Orobanchaceae), a new species from Turkey - Armağan, Meti̇n (Phytotaxa, 2018)
Pedicularis munzurdaghensis, a new species from Turkey, is described and illustrated. This species was found in the rocky limestone crevices in the Munzur Mountains between Tunceli and Erzincan, in Eastern Turkey. The new species is compared with those it is morphologically close, P. cadmea, P. arguteserrata, and P. anthemifolia.